Process on biological nitrogen removal technology of ammonia- nitrogen wastewater from ion-type rare earth mines - FAN Cunwen; GUO Peijie; HU Yujia; LIU Xinfu; QIU Qingrong; SU Hao; ZHANG Dachao (Gongye shui chuli)
Ammonium sulfate is a commonly used leaching agent in the mining process of southern ion-type rare earth mines, which causes large quantities of mine ammonia-nitrogen wastewater under the leaching action of rainwater even after stopping mining for a long time. The typical characteristics of ion-type rare earth mine ammonia-nitrogen wastewater are extreme low C/N, coexistence of ammonia and nitrate, which increased the cost and difficulty of nitrogen removal. Taking Ganzhou rare earth mining area, which had the largest amount of ionic rare earth resources in China, as an example, the water quantity and quality characteristics of ammonia-nitrogen wastewater from ion-type rare earth mines were analyzed. The process technology characteristics of existing ion-type rare earth mine wastewater treatment engineering practices were compared, and theoretical cost analysis was conducted. Based on the analysis of the advantages and disadvantages of new biological nitrogen removal technologies such as Anammox in the treatment of ammonia-nitrogen wastewater from rare earth mines, a combined process of partial denitrification-partial nitrification-Anammox was proposed to improve the effluent quality and reduce energy, which was proved to be the best process for removing nitrogen from ammonia-nitrogen wastewater of ionic rare earth mines.